2021
DOI: 10.1002/jor.25198
|View full text |Cite
|
Sign up to set email alerts
|

Age‐ and sex‐specific differences in ACL and ACL bundle size during adolescent growth

Abstract: Anterior cruciate ligament (ACL) injuries are increasingly common in adolescents, and injuries in this age‐group are associated with many unique challenges. Recent large animal studies suggest that the size and function of the major bundles of the ACL change differently throughout skeletal growth. To better aid clinical treatment of pediatric partial ACL tears and better predict outcomes from age‐specific treatments, there is a need to measure changes in ACL bundle size in humans during growth. As such, the ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Several studies, as listed in a recent systematic review, 18 have shown smaller ACLs in females compared to males, across a number of parameters including ACL length, CSA, volume, and mass, using cadaveric and imaging‐based measurements 3,7,19–21 . These sex‐specific differences have been found to emerge in adolescence, with one recent study showing that sex differences in ACL CSA emerge as early as 11 years of age even after adjusting for body size 20 and another study showing sex differences in ACL CSA and ACL length emerging at 13 years of age 21 . Moreover, a range of anthropometric measures (i.e., body weight, height, and body mass index [BMI]), along with several anatomical features of the knee joint (i.e., bicondylar width and intercondylar notch size) have been shown to correlate to ACL CSA 1–3,7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies, as listed in a recent systematic review, 18 have shown smaller ACLs in females compared to males, across a number of parameters including ACL length, CSA, volume, and mass, using cadaveric and imaging‐based measurements 3,7,19–21 . These sex‐specific differences have been found to emerge in adolescence, with one recent study showing that sex differences in ACL CSA emerge as early as 11 years of age even after adjusting for body size 20 and another study showing sex differences in ACL CSA and ACL length emerging at 13 years of age 21 . Moreover, a range of anthropometric measures (i.e., body weight, height, and body mass index [BMI]), along with several anatomical features of the knee joint (i.e., bicondylar width and intercondylar notch size) have been shown to correlate to ACL CSA 1–3,7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…An orthopedic surgeon with >10 years of experience in sports surgery and an experienced musculoskeletal radiologist examined the MRIs and measured the 17 morphological parameters using standard techniques previously described in the literature. [8,9,[12][13][14][15][16][17][18] The doctors who performed the measurements were blinded to the patient records. All MRIs were taken with a 1.5-T scanner (MAGNETOM Symphony; Siemens AG, Erlangen, Germany) with a 3-mm section thickness.…”
Section: Methodsmentioning
confidence: 99%
“…[12] The ACLW in the coronal section was determined by measuring the cross-sectional area made from the distal third of the ligament. [8] In the sagittal section, the angle between the orthogonal line of the longitudinal axis of the tibia and the line formed between the femur and tibial attachment of the ligament was measured and recorded as the ACLIA. [12] The ISI was defined as the ratio of the patellar tendon length to the maximum patella length.…”
Section: Methodsmentioning
confidence: 99%
“…Our group, along with others, have used a porcine model to understand structural and functional changes of the ACL throughout skeletal growth, including progression through adolescence [2328]. We have shown similar size and functional changes within the human and porcine ACL, making this a good model to study changes during adolescence [23,29]. The size of the porcine ACL diverges in males and females around the point of sexual maturity, mainly within the two distinct bundles of the ACL, the anteromedial (AM) and posterolateral (PL) bundles [30].…”
Section: Introductionmentioning
confidence: 99%